Kinetics of the Water Release of Hygroscopic Acrylamide Gel Embedded in Calcium Chloride by Thermogravimetric Analysis (Global Journal of Science Frontier Research, 2023)
Abstract not found
Keywords: steam harvesting; dew collection; freshwater; desiccants; thermoresponsive